A mechanistic investigation of anti-elimination in (Z)-1, 2-bis(arylseleno)-1-alkenes and their sulfur analogs1. Issue 21 (7th June 2015) - Tarao, Asami; Tabuchi, Yukako; Sugimoto, Eri; Ikeda, Miki; Uchimoto, Hitomi; Arimitsu, Kenji; Kimura, Hiroyuki; Kawasaki, Ikuo; Kawahata, Masatoshi; Yamaguchi, Kentaro; Nishide, Kiyoharu
<x xml:space="preserve">Abstract</x> Selenoxide anti-elimination in (Z)-1, 2-bis(arylseleninyl)-1-alkenes is induced by the Se⋯O interaction, whereas the sulfur analogs lacks this type of nonbonding interaction.